Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0246480
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of statin and fibrate monotherapy: A systematic review and meta-analysis of head-to-head randomized controlled trials

Abstract: Objective To assess whether in adults with dyslipidemia, statins reduce cardiovascular events, mortality, and adverse effects when compared to fibrates. Methods Systematic review and meta-analysis of head-to-head randomized trials of statin and fibrate monotherapy. MEDLINE, EMBASE, Cochrane, WHO International Controlled Trials Registry Platform, and ClinicalTrials.gov were searched through October 30, 2019. Trials that had a follow-up of at least 28 days, and reported mortality or a cardiovascular outcome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
3
0
2
Order By: Relevance
“…A systematic review and meta-analysis of 19 head-to-head randomized controlled trials showed that, although there was no significant difference between statin monotherapy and fibrate monotherapy for cardiovascular mortality or major cardiovascular events, adverse events were less frequent with statins than with fibrates. 23 Interestingly, another meta-analysis of 9 studies revealed that kidney-related adverse events (ie, events corresponding to a >50% increase in baseline creatinine exceeding the upper limit of normal) were significantly more common in patients receiving statin-fibrate dual therapy than in those receiving fibrate monotherapy. 24 In view of these findings, general practitioners may be reluctant to treat patients with fibrates and may prefer to prescribe these medications to patients with statin intolerances.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of 19 head-to-head randomized controlled trials showed that, although there was no significant difference between statin monotherapy and fibrate monotherapy for cardiovascular mortality or major cardiovascular events, adverse events were less frequent with statins than with fibrates. 23 Interestingly, another meta-analysis of 9 studies revealed that kidney-related adverse events (ie, events corresponding to a >50% increase in baseline creatinine exceeding the upper limit of normal) were significantly more common in patients receiving statin-fibrate dual therapy than in those receiving fibrate monotherapy. 24 In view of these findings, general practitioners may be reluctant to treat patients with fibrates and may prefer to prescribe these medications to patients with statin intolerances.…”
Section: Discussionmentioning
confidence: 99%
“…Una RS publicada por Sahekbar et al 125 reportó que el fenofibrato disminuyó los niveles de ApoC3 (DMP: –4.78 mg/dl; IC 95%: –6.95 a –2.61) en 10 estudios clínicos (477 participantes). Una RS publicada por Blais et al 126 en 2021 tuvo como objetivo evaluar la eficacia de los fibratos en comparación con las estatinas como monoterapias para disminuir la mortalidad y los eventos cardiovasculares. Los autores incluyeron 19 estudios clínicos, sin embargo, los tiempos de seguimiento fueron muy cortos (desde 10 semanas a dos años) y los resultados del metaanálisis no mostraron diferencias en la mortalidad cardiovascular (RM: 2.35; IC 95%: 0.94-5.86), eventos cardiovasculares (RM: 1.15; IC 95%: 0.80-1.65).…”
Section: Recomendaciones Clínicasunclassified
“…La frecuencia de eventos adversos fue menor en el grupo tratado con estatinas (RM: 0.57; IC 95%: 0.36-0.91). Debido a que los estudios fueron diseñados para evaluar eficacia para modificar el perfil de lípidos, no fue posible evaluar el impacto en desenlaces cardiovasculares y mortalidad 126 .…”
Section: Recomendaciones Clínicasunclassified
“…Pharmacological PPARα agonists, such as fibrates, are clinically used to normalize blood lipid profile, particularly to lower concentrations of cholesterol and low-density lipoprotein fractions [ 47 ]. Fenofibrate and gemfibrozil are the most widely prescribed drugs from a fibrate group, and they are generally very well tolerated [ 48 ]. Nevertheless, some adverse effects have been reported in patients chronically taking fibrates, with myopathy and rhabdomyolysis being the most common problems [ 49 ].…”
Section: Peroxisome Proliferator-activated Receptor Alpha (Pparα) and Its Role In Inflammationmentioning
confidence: 99%